Answer:
x = y = - 2
Explanation:
Using the rule of radicals/ exponents
=
,
=
,
=
![a^(mn)](https://img.qammunity.org/2022/formulas/mathematics/high-school/cmsd2gfv2pql9zrvq0ifgu4i63g47fufzy.png)
Given
=
, then
=
![(1)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/f0qcv9cek84ihznc3s7uf39dlk9xfru67q.png)
=
![2^(-1)](https://img.qammunity.org/2022/formulas/mathematics/college/idkfnt7zzfk8htfzexv6opf4l75qgqd3sz.png)
Since the bases on both sides are equal, both 2 , then equate exponents
= - 1 ( multiply both sides by x )
2 = - x , that is
x = - 2
Similarly
=
, then
=
![(1)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/8c4su5tuu474mta5yxnqkrtvi2n4u8590o.png)
=
![3^(-1)](https://img.qammunity.org/2022/formulas/mathematics/middle-school/9w7ijuvafcc03hb7kx8zham5vum9493627.png)
Equating the exponents gives
= - 1 ⇒ - y = 2 ⇒ y = - 2